Hong Kong Mothers and Emotional Sustainability via UN Sustainable Development Goal#3 Wellness and #16 Peace - Shirley MC Yeung (Sekolah Tinggi Manajemen IPMI, 2021)
The proposed project is expected to attract a target of 500 postnatal women (less than 3 months after delivery) for a half-year business intervention pilot project named “ Local Pui Yu” / postnatal assistant center to pilot this service with the support from IT companies on the techniques and devices to be needed to create the impacts and make the impacts transparent. And, it is expected that IT companies and/ or invited NGOs can support the total costs, for example, marketing cost, education material cost, and recruitment cost in employing midwives. Consequently, a new and easier method to deliver professional education with revenue creation business model will be created to support women and families, promote women, family and neonatal help; enhancing the awareness of women health, family and work balance issues.